The application of society 5.0 community service in Kulon Progo district - Anindyajati, Adhi (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2021)
Academic community service (KKN – kuliah kerja nyata) normally involves on-field activities and interaction between students and local communities. The emerge of covid-19 pandemic led to social distancing, a less ideal situation for on-field community service. Meanwhile, the advance of information technology brought society toward the fifth era. At this situation, the concept of society 5.0 was applied on community service conducted in Kulon Progo district, Yogyakarta. Programs dedicated to improve local community were arranged without direct contact with community members, but utilizing online information to identify the potentials in the location under study and challenges faced by the community. Through literature study, proposed improvement on the potentials and solutions for the problems were developed. The results were presented as ebook or video offering educative and informative contents that can be beneficial for community empowerment.